2022
DOI: 10.1002/adom.202102055
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Sensitive β‐Ga2O3 Solar‐Blind Photodetector with High‐Density Al@Al2O3 Core−Shell Nanoplasmonic Array

Abstract: β‐Ga2O3 solar‐blind photodetectors (PDs) are attracting great attention for broad applications. However, their detection sensitivities are still lower than expected after tremendous efforts. The phenomenon of localized surface plasmon resonance (LSPR) offers another approach beyond conventional techniques to engineer the photodetection performance, but extending the plasmonic properties into the deep‐ultraviolet region faces severe challenges, among which strictly controlling the nanostructures structural prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 71 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…For example, by modifying a well-defined Al@Al 2 O 3 core-shell nanostructure array, Qian et al demonstrated an improvement in the responsivity of the 𝛽-Ga 2 O 3 photodetector by more than four times. [134] Therefore, by reasonably matching and coupling these non-precious metal optical antennas with 2DLMs, the photosensitivity of 2DLM photodetectors can theoretically be significantly improved.…”
Section: Non-noble Metal Optical Antenna Promoted 2dlm Photodetectorsmentioning
confidence: 99%
“…For example, by modifying a well-defined Al@Al 2 O 3 core-shell nanostructure array, Qian et al demonstrated an improvement in the responsivity of the 𝛽-Ga 2 O 3 photodetector by more than four times. [134] Therefore, by reasonably matching and coupling these non-precious metal optical antennas with 2DLMs, the photosensitivity of 2DLM photodetectors can theoretically be significantly improved.…”
Section: Non-noble Metal Optical Antenna Promoted 2dlm Photodetectorsmentioning
confidence: 99%
“…Qian et al. combined Al/Al2normalO3 core–shell nanostructure arrays with β-Ga2O3 solar-blind photodetectors by the nanosphere lithography, which exhibits a sharp plasmon resonance peak at 235 nm belonging to the solar-blind UV region (200–280 nm) that hardly reaches the surface of the Earth [357] . An excellent responsivity (216 A/W) and ultrahigh specific detectivity (4.22×1015 Jones) are achieved.…”
Section: Hot-carrier-based Applicationsmentioning
confidence: 99%
“…Solar-blind photodetectors have attracted widespread attention due to their extensive applications such as optical communication, heavy weapon monitoring, missile tracking, ozone hole monitoring, imaging technology and explosion and flame detection. [1][2][3][4] Wide band gap semiconductors are deemed as promising materials for manufacturing SBPDs. Among them, Ga 2 O 3 with an ultra-wide bandgap of 4.4-5.3 eV corresponding to the solar-blind spectrum region between 238 and 280 nm is a natural material used for solar-blind ultraviolet photodetectors because it does not exist on the surface of the earth due to the strong absorption of deep ultraviolet light by stratospheric ozone.…”
Section: Introductionmentioning
confidence: 99%